The Effect Of Percussive Therapy On Musculoskeletal Performance And Experiences Of Pain: A Systematic Literature Review - Lorna Sams; Ben L Langdown; Joan Simons; Jitka Vseteckova (North American Sports Medicine Institute, 2023)
# Background There is a lack of specific research on the effect of percussive therapy (PT) delivered by massage guns on physiological adaptations. This systematic literature review investigates research conducted on the effects of PT interventions on performance in strength and conditioning settings, and on experiences of musculoskeletal pain. # Purpose To determine the effect of PT delivered by massage guns on physiological adaptations: muscle strength, explosive muscle strength and flexibility, and experiences of musculoskeletal pain. # Study Design Systematic literature review. # Methods Data sources (CINAHL, Cochrane Library, Psychinfo, PubMed, SportDISCUS and OpenGrey) were searched from January 2006 onwards for full text literature in any language involving adult populations receiving PT delivered by massage guns, directly to any muscle belly or tendon, with comparisons to an alternative treatment, placebo or no treatment. Literature with outcomes relating to acute or chronic physiological adaptations in muscle strength, explosive muscle strength, flexibility or experiences of musculoskeletal pain were included. Articles were assessed for quality using the Critical Appraisal Skills Programme and PEDro scores. # Results Thirteen studies met the inclusion criteria. All studies had limitations in methodological quality or reporting of findings but still included contextually-rich details that contributed to the overall narrative synthesis. A significant relationship was found between a single application of PT delivered by massage guns and an acute increase in muscle strength, explosive muscle strength and flexibility, with multiple treatments eliciting a reduction in experiences of musculoskeletal pain. # Conclusion PT delivered by massage guns can help improve acute muscle strength, explosive muscle strength and flexibility, and reduce experiences of musculoskeletal pain. These devices may provide a portable and cost-effective alternative to other forms of vibration and interventions.